Influence of Meteorological Conditions and Fire Hotspots on PM0.1 in Northern Thailand during Strong Haze Episodes and Carbonaceous Aerosol Characterization - Chaiyoth Sresawasd; Thaneeya Chetiyanukornkul; Phuchiwan Suriyawong; Surajit Tekasakul; Masami Furuuchi; Mitsuhiko Hata; Rachane Malinee; Perapong Tekasakul; Racha Dejchanchaiwong (Aerosol and Air Quality Research)
Abstract Northern Thailand has long been severely affected by haze from biomass burning containing fine and ultrafine aerosols in the dry period. The carbonaceous PM0.1 comprising elemental carbon (EC) and organic carbon (OC) collected during the haze and non-haze periods in Chiang Mai, Thailand was investigated. The PM0.1 levels during the haze periods were about 3 times higher than the non-haze periods, a significant increase. PM0.1 concentration was strongly correlated with atmospheric relative humidity and the number of forest fire hotspots. Carbonaceous aerosol characteristics in PM0.1 were analyzed with the thermal/optical transmittance (TOT) method following the IMPROVE protocol. The concentrations of OC and EC, distribution of OC and EC and OC/EC ratios in PM0.1 were evaluated. Average OC and EC mass concentrations in PM0.1 were 6.8 ± 2.7 and 1.4 ± 0.5 µg m−3 during the haze periods, significantly higher than those during the non-haze periods; 1.9 ± 0.9 and 0.5 ± 0.2 µg m−3. The OC/EC ratio increased linearly with the number of hotspots. This indicated significant contribution from biomass burning to the PM0.1. This was strongly supported by the 48-hr backward trajectory simulation, that indicated both domestic and transboundary aerosol transports. Because both organic and elemental carbon are the light-absorbing carbonaceous aerosols, the increase during the haze periods contributed to regional air quality and climate. This study enhances the understanding of PM0.1 behavior in Chiang Mai, Thailand, during the haze periods in upper southeast Asia.